2015
DOI: 10.1007/8904_2015_407
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Bone Mineral Density and Architecture in a Patient with Gaucher Disease Using Teriparatide

Abstract: Gaucher disease is an autosomal recessive lysosomal storage disorder caused by deficiency of the enzyme acid beta-glucosidase (glucocerebrosidase)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…Osteopetrosis density measurement were elevated in comparison to reference data. These findings are consistent with what has been previously reported in examining bone microarchitecture in sub-types of IBEMs using HR-pQCT [14][15][16][17][18][19][20][21]. Both cortical and trabecular bone play a crucial role in maintaining bone integrity and deficits in each have been shown to increase fracture risk [24,36,37].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Osteopetrosis density measurement were elevated in comparison to reference data. These findings are consistent with what has been previously reported in examining bone microarchitecture in sub-types of IBEMs using HR-pQCT [14][15][16][17][18][19][20][21]. Both cortical and trabecular bone play a crucial role in maintaining bone integrity and deficits in each have been shown to increase fracture risk [24,36,37].…”
Section: Discussionsupporting
confidence: 91%
“…To date, single case reports and case studies on individual IBEMs have been published examining bone microarchitecture using HR-pQCT. We and others have reported impaired bone density and microarchitecture when compared to healthy controls, with the exception of osteopetrosis, where bone density and microarchitecture is significantly elevated [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Due to its increased surface area, trabecular bone remodeling is evident sooner than cortical bone. Previous work has demonstrated increased trabeculae thickness, lower trabeculae separation, and increased BMD and trabeculae density in GD patients following ERT (Khan et al, 2015). In the current study, GD patients treated with ERT also demonstrated higher trabeculae thickness, lower trabeculae separation and higher trabeculae density compared to HC individuals.…”
Section: Discussionsupporting
confidence: 68%
“…Journal Pre-proof [115]. Another proposal is a combination therapy with romosozumab, a monoclonal antibody that binds sclerostin, leading to its dual effect of increasing bone formation and decreasing bone resorption [116].…”
Section: Effect Of Therapies On Skeletal Manifestations In Gaucher Patientsmentioning
confidence: 99%